Monitoring to assess the recovery status of imperiled species should be commensurate with the criteria for their recovery: the case of Bull Trout - Whitesel, Timothy A. (Frontiers in Conservation Science, 2025)
The classification of a population as imperiled may lead to the development of a formal recovery plan with specific legal requirements. Rigorous recovery plans typically include criteria by which to gauge population recovery and monitoring plans to guide evaluations of whether criteria are achieved. Monitoring plans have traditionally focused on ecological characteristics. However, there is an increasing frequency of recovery plans and criteria focused on the reduction of threats. Traditional monitoring plans often match imperfectly with threats-based criteria. For example, Bull Trout in the U.S. are currently considered imperiled. Their recovery plan and criteria call for 75-100% of the primary threats to their persistence to be managed effectively. Incongruous with these criteria, monitoring plans to inform the recovery status of Bull Trout have generally focused on characteristics such as abundance, trends in abundance, distribution and connectivity. Bull Trout in the Elwha River are discussed as an example of threats being explicitly monitored and informing status. For species such as Bull Trout, the most useful monitoring plan for assessing recovery status would guide explicit and quantitative evaluations of threat scope and severity, determine how effectively threats are being managed, and be commensurate with the criteria for recovery.